The relationship between parenting style and the success rate of toilet training in children with intellectual disabilities - Ninda Dewi Anjani Putri; Istinengtiyas Tirta Suminar; Armenia Diahsari (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2026)
Background: Toilet training is an essential developmental milestone that supports children’s independence; however, children with intellectual disabilities often experience developmental delays and require consistent guidance and appropriate parenting strategies. Purpose: to analyze the relationship between parenting styles and toilet training success among children with intellectual disabilities. Method: This quantitative cross-sectional study the respondents were parents of children enrolled at Extraordinary School Dharma Bhakti Piyungan and Extraordinary School Dharma Putra Semin, selected using total sampling (n = 56). Data were collected using parenting style and toilet training success questionnaires and analyzed using the Chi-Square test. Results: The results showed that 38 children (62,5%) were successful in toilet training, while 18 children (32,1%) were unsuccessful. Based on the dominant parenting style categories, 45 children (80,4%) with democratic parenting, 35 children (62,5%) were successful, whereas all children with permissive parenting (10.7%) were unsuccessful. In authoritarian parenting, 3 children (5.4%) were successful, and 2 children (3.6%) were unsuccessful.The Chi-Square test demonstrated a significant relationship between parenting style and toilet training success (p = 0.001), with a strong association (Cramer’s V = 0.515). Conclusion: These findings indicate that parenting style plays an important role in supporting toileting independence among children with intellectual disabilities. Structured, consistent, and responsive parenting approaches are essential in enhancing toilet training success.